Quality of Organic Emmer Wheat and Possibility of Its Utilization - Lacko-Bartošová, Magdaléna; Čurná, Veronika (Agrobiodiversity for Improving Nutrition, Health and Life Quality, 2020)
The increasing popularity of organic agriculture and health food products has led to a renewed interest in a hulled wheat species such as emmer wheat (Triticum dicoccon Schrank). Knowledge on quality traits is required for its effective and efficient usage. The objective of presented study was to determine rheological properties of dough and pasta quality of four organic emmer wheat varieties cultivated in the south region of the Slovak Republic. A field stationary experiment was carried out at the Research Experimental Station of the Faculty of Agrobiology and Food Resources, Slovak University of Agriculture, Dolná Malanta. The rheological parameters of emmer were significantly influenced by varieties and weather conditions during vegetative periods. Dough of emmer wheat was characterized by high water absorption (60.53% on average) but with low stability (1.45 min on average). Farinograph quality number ranged between 12.38 mm and 30.38 mm. Rheological parameters indicated worse breadmaking quality of emmer. The quality of white flour and wholegrain flour pasta was expressed by cooking time, water absorption, cooking loss and swelling. Wholegrain pasta was characterized by longer cooking time and by higher cooking loss (due to presence of the bran in a wholegrain flour) than white flour pasta, absorbed lower amount of water during cooking and reached lower swelling than white flour pasta. Given the worse possibilities of utilization for proofing emmer dough, breeding programs for improving rheological properties have been undertaken to genetically improve emmer gluten strength. Nevertheless, emmer wheat flour, mainly wholegrain flour, is suitable for pasta manufacturing industry.